Genome sequencing provides insight into the reproductive biology, nutritional mode and ploidy of the fern pathogen Mixia osmundae. Issue 2 (24th December 2013) - Toome, Merje; Ohm, Robin A.; Riley, Robert W.; James, Timothy Y.; Lazarus, Katherine L.; Henrissat, Bernard; Albu, Sebastian; Boyd, Alexander; Chow, Julianna; Clum, Alicia; Heller, Gregory; Lipzen, Anna; et al.
Summary Mixia osmundae (Basidiomycota, Pucciniomycotina) represents a monotypic class containing an unusual fern pathogen with incompletely understood biology. We sequenced and analyzed the genome of M. osmundae, focusing on genes that may provide some insight into its mode of pathogenicity and reproductive biology. Mixia osmundae has the smallest plant pathogenic basidiomycete genome sequenced to date, at 13.6 Mb, with very few repeats, high gene density, and relatively few significant gene family gains. The genome shows that the yeast state of M. osmundae is haploid and the lack of segregation of mating genes suggests that the spores produced on Osmunda spp. fronds are probably asexual. However, our finding of a complete complement of mating and meiosis genes suggests the capacity to undergo sexual reproduction. Analyses of carbohydrate active enzymes suggest that this fungus is a biotroph with the ability to break down several plant cell wall components. Analyses of publicly available sequence data show that other Mixia members may exist on other plant hosts and with a broader distribution than previously known.